Mathematical Modeling of Whispering Gallery Mode Resonators for High-Sensitivity Refractive Index Sensing - Lazem, Farah A.; Hammod, Haider Y.; Mahmood, Aseel I. (Iraqi Journal of Physics, 2025)
In this study, the Single-Mode Fiber (SMF) was examined in a theoretical investigation of the impact of the medium on the two Whispering Gallery Mode Resonator (WGMR) models using MATLAB software. It was found that the Free Spectral Range (FSR) has an inverse relationship with the resonator radius, and it was equal to 0.33 THz. The low FSR value is caused by the big microsphere resonator. A high Q-factor is defined as 0.175 x 105. The resonance spectrum was found to diminish when the surrounding media’s refractive index rose. The WGMR’s evanescent field interacts with the external medium more strongly when the surrounding environment’s refractive index increases. The resonant modes’ boundary conditions were altered by this interaction, which raises the modes’ effective refractive index. The WGMR resonance frequency may also shift as a result of changes in the surrounding medium refractive index. To achieve high-resolution sensing, the surrounding medium of the spherically shaped WGMR was altered at a step of 0.002 in the range of 1.33 to 1.35. As for the sensitivity value, a value of (-) 100.152 THz/RIU was obtained, which is considered a good value for use as a sensor.